Respuesta :

Answer:

D

Step-by-step explanation:

Swap x for y and y for x. Then solve the equation for y.

Answer:

option D

y = -1/3x + 2/7

Step-by-step explanation:

y = -3x + 6/7

Step1

Interchange the variables

x = -3y + 6/7

Step2

Solve for y

x - 6/7 = -3y

y = [tex]\frac{\frac{6}{7}-x }{3}[/tex]

step3

Solve for y and replace with f−1(x)

[tex]f^{-1}(x)[/tex]=[tex]\frac{\frac{6}{7}-x }{3}[/tex]

step4

simplify

[tex]y ={\frac{6}{7(3)}-\frac{x}{3}}[/tex]

=[tex]{\frac{2}{7}-\frac{x}{3} }[/tex]